Assessment of free light chains in HCV‐positive patients with mixed cryoglobulinaemia vasculitis undergoing rituximab treatment. (20th April 2015) - Basile, Umberto; Gragnani, Laura; Piluso, Alessia; Gulli, Francesca; Urraro, Teresa; Dell'Abate, Maria T.; Torti, Eleonora; Stasi, Cristina; Monti, Monica; Rapaccini, Gian Ludovico; Zignego, Anna Linda
Abstract Background & Aims Mixed cryoglobulinaemia (MC) is an HCV‐related lymphoproliferative disorder characterized by the presence of circulating immune complexes called cryoglobulins. Treatment with anti‐CD20 monoclonal antibody rituximab is proved to be very useful, especially in patients ineligible to interferon‐based antiviral therapy. Recently, free light chain (FLC) κ/λ ratio and FLC patterns were associated with MC. The aim of this study was to evaluate changes in FLC‐κ, FCL‐λ, FLC ratio following rituximab treatment in patients with HCV‐related MC and to correlate FLC‐κ, FCL‐λ and FLC ratio values with therapy response. Patients and Methods We retrospectively enrolled 46 patients with HCV infection (26 females, 20 males), including 10 patients without signs/symptoms of MC‐related vasculitis, 36 with MC vasculitis. Clinical and biological data were recorded at baseline and 6 months after RTX treatment. Nephelometric measurement of serum FLCs was taken. Results The mean serum FLC‐κ level and FLC ratio were significantly higher in patients with MC, compared to HCV patients without MC and to blood donors. An abnormal FLC ratio at baseline correlated with the presence of cryoglobulins, C4 consumption, higher RF level and higher vasculitis rate. To evaluate the predictive value of FLCs, patients with MC were divided into two groups according to RTX therapy outcome (responders and no/partial responders). Abnormal baseline FLC ratio was significantly associated with no/partial response. Conclusions RTX treatment in HCV‐related MC induces a reduction in FLC‐κ and RF levels. Moreover, pretreatment FLC ratio, which can be easily assessed by a routine test, may be useful to predict response to this expensive treatment for patients with HCV‐related MC ineligible to IFN‐based therapy.